Cryptococcus neoformans and Cryptococcus gattii as causative causes of cryptococcosis in immunosuppressed patients: an integrative review (Research, Society and Development, 2023)
This study aimed to describe Cryptococcus neoformans and Cryptococcus gattii as causes of cryptococcosis in immunosuppressed patients. To carry out this integrative literature review, a survey of articles in the literature was carried out in the following databases: LILACS, BVS (virtual health library), PubMed and Scielo. The survey took place between October and December 2022. Cryptococcosis is considered a systemic mycosis that is commonly observed in immunosuppressed patients. The invasive fungal infection is provoked by the fungi Cryptococcus neoformans and Cryptococcus gattii that are found in the excreta of birds, mainly in faeces of pigeons. In humans, cryptococcal infection commonly occurs after the fungus is inhaled and involves lung colonization and meningeal involvement. Most patients diagnosed with cryptococcosis have an identified predisposition related to cellular immunosuppression. The most common propensity is HIV infection, but we can also cite situations that include prolonged treatment with corticosteroids, solid organ receptors, idiopathic CD4 lymphocytopenia, advanced malignancy, sarcoidosis and severe states of cellular immunosuppression. Immunosuppressed patients with cryptococcosis have reported dimensions of complications, including cryptococcal meningitis, case fatality rates, or other variables associated with these complications. Among the consequences of cryptococcosis in these patients, case studies of pulmonary cryptococcosis, cryptococcal osteomyelitis, mammary cryptococcosis, central nervous system infection, extrameningeal cryptococcosis, disseminated cryptococcosis, meningoencephalitis and cryptococcal meningitis were found. We conclude that cryptococcosis caused by Cryptococcus neoformans and Cryptococcus gattii is regularly reported in immunosuppressed patients, which significantly influences the severity and mortality rates from cryptococcosis.